1998
DOI: 10.7164/antibiotics.51.515
|View full text |Cite
|
Sign up to set email alerts
|

Pulchellalactam: A CD45 Protein Tyrosine Phosphatase Inhibitor from the Marine Fungus Corollospora pulchella.

Abstract: CD45 protein tyrosine phosphatase is a largemolecular mass transmembrane glycoprotein expressed on all hematopoietic cells except erythrocytes.1) It is a member of the receptor-like transmembrane protein tyrosine phosphatase2) (PTPase) family. Expression of CD45 has been shown to be important for activation of both B and T cells via their antigen-specific receptors3,4) and has generated considerable interest in the study of lymphocyte activation as well as a possible target for drug intervention in various aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 9 publications
0
29
0
1
Order By: Relevance
“…At present, there are five total syntheses reported for Pulchellalactam (1). [3 -7] Li et al [3] reported the first total synthesis of (1) in six-steps starting from N-boc-glycine in overall yield of 32%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there are five total syntheses reported for Pulchellalactam (1). [3 -7] Li et al [3] reported the first total synthesis of (1) in six-steps starting from N-boc-glycine in overall yield of 32%.…”
Section: Introductionmentioning
confidence: 99%
“…(Z ) Pulchellalactam (1), a pyrrolidinone isolated in 1997 from the marine fungus Corollospora pulchella by Alvi et al, [1] has been the focus of some attention owing to its potent inhibitory action against protein tyrosine phosphatase, (PTP) CD45, which in turn activates B and T cells. Protein tyrosine phosphatase has been a target implicated in autoimmune and antiinflamatory diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulchellalactam is isolated from the marine fungus Corollospora pulchella, exhibiting high inhibitory activity toward CD45 (98JAN515). In order to have sufficient amounts for biological screening and evaluation and its geometry determination, syntheses of both E-pulchellalactam 70 and Z-pulchellalactam 71 was attempted.…”
Section: Containing One Heteroatommentioning
confidence: 99%
“…8,10 Synthetic fimbrolide 2 (R = Br) was found to reduce P. aeruginosa levels in the lungs by three orders of magnitude in a pulmonary mouse model. 9 Intrigued by the exocyclic iso-propyl moiety in the structurally related natural product pulchellalactam 12 3 as well as the presence of the similar tert-butyl group in various antibacterial compounds, 13,14 we set out to synthesize brominated furanones 4 (R 1 or R 2 = Br) carrying a vinylic iso-propyl or tert-butyl substituent at the C5 position ( Figure 2). Compounds where the C4-bromine was switched to the C3 position were also targeted to afford a more comprehensive library of furanones for structure-function investigations.…”
Section: Introductionmentioning
confidence: 99%